2016
DOI: 10.1161/circimaging.116.004129
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fractional Flow Reserve Assessment With Demand Stress Myocardial Contrast Echocardiography in Angiographically Intermediate Coronary Stenoses

Abstract: Intracoronary pressure-derived fractional flow reserve (FFR) provides physiologically relevant information in determining the functional significance of a coronary stenosis, but provides no data regarding CBF. 6,11,12 An FFR-guided approach for revascularization is associated with improved clinical outcomes in multivessel CAD, 6 and abnormal values with this technique clearly identify a higher risk subgroup of patients. Although they do not seem to benefit from Background-Real-time myocardial contrast echocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 26 publications
3
16
0
2
Order By: Relevance
“…Importantly, for assessments of coronary physiology during cardiac catheterization, FFR and CFR can now be measured simultaneously with combined pressure sensor-and flow sensor-tipped guidewires. 204 More recently, quantitative estimates of myocardial perfusion from Doppler echocardiography 205,206 and contrast echocardiography 207 have emerged as having clinical value.…”
Section: Ffrmentioning
confidence: 99%
“…Importantly, for assessments of coronary physiology during cardiac catheterization, FFR and CFR can now be measured simultaneously with combined pressure sensor-and flow sensor-tipped guidewires. 204 More recently, quantitative estimates of myocardial perfusion from Doppler echocardiography 205,206 and contrast echocardiography 207 have emerged as having clinical value.…”
Section: Ffrmentioning
confidence: 99%
“…In this issue of Circulation: Cardiovascular Imaging, Wu et al 5 compared RTMCE CBF (ie, capillary) and left ventricular wall motion abnormality (LVWMA) to FFR in 58 patients with 67 intermediate coronary stenosis, ranging in severity from 50% to 80%. Dobutamine (n=32) or exercise (n=26) stress was performed before angiography.…”
Section: See Article By Wu Et Almentioning
confidence: 99%
“…However, 28 of 49 FFR-negative stenoses (57%) also had abnormal CBF and 24 of 49 (49%) had abnormal wall motion. Wu et al 5 concluded that a large percentage of intermediate stenoses with nonischemic FFR values (ie,>0.80) had reduced MCE CBF during demand stress, resulting in myocardial ischemia. Thus, abnormal CBF during demand stress RTMCE had high sensitivity (94%) for detecting a hemodynamically significant epicardial stenosis (ie, abnormal FFR) but a low specificity (57% for nonischemic FFR).…”
Section: See Article By Wu Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Weitere Fortschritte leistete die kardiale MRT-Diagnostik, die heute zum Standardverfahren avancierte aufgrund der fehlenden Strahlenbelastung, aber auch methodischer Fortschritte. Die Kontrastechokardiographie erlebte ebenfalls einen Innovationsschub, als das "highpower imaging" eingeführt wurde, welches die Mikrokavitationen zerstört [36][37][38][39][40][41][42][43]. In der Folge wird die Wiederanfärbung des Myokards beurteilt, um eine Abschätzung von Perfusionsstörun-gen zu erreichen.…”
unclassified